2003
DOI: 10.1099/vir.0.19250-0
|View full text |Cite
|
Sign up to set email alerts
|

A promoter within the E6 ORF of human papillomavirus type 16 contributes to the expression of the E7 oncoprotein from a monocistronic mRNA

Abstract: Human papillomavirus type 16 (HPV-16) has the capacity to transform human primary keratinocytes. Maintenance of the transformed phenotype requires constitutive expression of the oncoproteins E6 and E7. The low-risk HPV types express E7 from monocistronic mRNA, but for the high-risk types, no mRNA that encodes E7 as the first open reading frame (ORF) has been identified. We recently identified a transcription initiation site within the E6 ORF of HPV-16 at nt 542. In the present study we have characterized the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…It was first found as an enhancer-binding factor of the SV40 (simian virus 40) late transcription in vitro by Mermod and colleagues [5]. In many studies, AP4 was found to participate in cellular differentiation, cell proliferation [6][7][8][9][10], cell cycle regulation, and apoptosis [11][12][13][14][15][16]. More recent findings show that AP4 is also involved in pathological conditions, for example, AP4 is highly expressed in colon carcinoma, breast cancer, and prostate cancer [15,17,18] and that AP4 suppresses MCF-7 cell proliferation via enhancing the levels of SHP1 and JNK activation [19].…”
Section: Introductionmentioning
confidence: 99%
“…It was first found as an enhancer-binding factor of the SV40 (simian virus 40) late transcription in vitro by Mermod and colleagues [5]. In many studies, AP4 was found to participate in cellular differentiation, cell proliferation [6][7][8][9][10], cell cycle regulation, and apoptosis [11][12][13][14][15][16]. More recent findings show that AP4 is also involved in pathological conditions, for example, AP4 is highly expressed in colon carcinoma, breast cancer, and prostate cancer [15,17,18] and that AP4 suppresses MCF-7 cell proliferation via enhancing the levels of SHP1 and JNK activation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several other promoters which might play an important role in the viral life cycle have been identified [9][10][11][12][13]. Transcription of HPV late genes is only activated as HPVpositive cells start to differentiate [14,15].…”
Section: Regulation Of Transcriptionmentioning
confidence: 99%
“…In India, it has been reported that 130,000 cases and 70-75,000 death occurred annually, suggesting that the cervical cancer is one of the major cancers in India [5]. Based on the carcinogenicity, HPV can be divided into two groups: high-risk types such as HPV 16 and 18 and low-risk types such as HPV type 6 and 11 [6]. More than 70% of cervical cancer is caused by both HPV type 16 and 18.…”
Section: Introductionmentioning
confidence: 99%